2014
DOI: 10.4062/biomolther.10.4062/biomolther.2014.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atomoxetine on Hyper-Locomotive Activity of the Prenatally Valproate-Exposed Rat Offspring

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. www.biomolther.orgA substantial proportion of patients with autism spectrum disorder (ASD) display hyperactivity as a comorbid symptom. Exposure to valproic acid (VPA) during pregnancy produces ASD-like core b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As for predictive validity, some studies tested the ability of 'offlabel' drugs commonly prescribed to autistic patients to ameliorate the behavioral and brain abnormalities displayed by VPA-exposed animals. For instance, Choi et al (2014) found that the attention deficit hyperactivity disorder medication, atomoxetine, mitigated the hyperlocomotion displayed by VPA-exposed rats, whereas methylphenidate was ineffective. As atomoxetine is a selective noradrenaline transporter inhibitor, whereas methylphenidate inhibits both the noradrenaline and the dopamine transporters, these results suggest that abnormalities in the noradrenaline transporter may underlie the hyperactive phenotype in VPA-exposed animals.…”
Section: Rodent Models Of Autism Spectrum Disorders Based On Environmental Factorsmentioning
confidence: 99%
“…As for predictive validity, some studies tested the ability of 'offlabel' drugs commonly prescribed to autistic patients to ameliorate the behavioral and brain abnormalities displayed by VPA-exposed animals. For instance, Choi et al (2014) found that the attention deficit hyperactivity disorder medication, atomoxetine, mitigated the hyperlocomotion displayed by VPA-exposed rats, whereas methylphenidate was ineffective. As atomoxetine is a selective noradrenaline transporter inhibitor, whereas methylphenidate inhibits both the noradrenaline and the dopamine transporters, these results suggest that abnormalities in the noradrenaline transporter may underlie the hyperactive phenotype in VPA-exposed animals.…”
Section: Rodent Models Of Autism Spectrum Disorders Based On Environmental Factorsmentioning
confidence: 99%